Developmental and Genotypic Variation in Leaf Wax Content and Composition, and in Expression of Wax Biosynthetic Genes in Brassica oleracea var. capitata - Laila, Rawnak; Robin, Arif Hasan Khan; Yang, Kiwoung; Park, Jong-In; Suh, Mi Chung; Kim, Juyoung; Nou, Ill-Sup (Frontiers in Plant Science, 2017)
Cuticular waxes act as a protective barrier against environmental stresses. The present study was conducted to investigate the developmental and genotypic behaviour in wax formation of cabbage lines, with a view to understand the related morphology, genetics and biochemistry. Wax deposition increased with leaf age in five-month-old plants. The high-wax lines had dense, prominent and larger crystals on the leaf surface compared to low-wax lines under a scanning electron microscope. The waxy compounds in all cabbage lines were predominately C29-alkanes, -secondary alcohols and -ketones. Relative expression of wax biosynthetic genes in the first-formed leaf of the highest-wax line was consistently higher at three sampling points collected at weekly intervals but decreased in other genotypes with increasing leaf age. Similarly, in five-month-old cabbage heads, expression of the majority of the genes decreased from the inner leaves to the outer leaves in the low-wax lines in contrast to the highest-wax line suggesting a declining trend in wax deposition in low-wax lines. In 10-week-old plants, expression of wax biosynthetic genes followed a quadratic function and that generally increased from the youngest leaf to position 4 but greatly declined at the older leaves. Principal component analysis revealed that the higher relative expression of LTP2 genes in the lowest-wax line and the higher relative expression of CER3 in the highest-wax line probably determined the comparatively lower and higher wax content in those two lines, respectively. The results of this study improve our understanding of wax formation behaviour and genetics of cabbage lines during development.